O Sistema de Avaliação do Desempenho Escolar de Jaguaruana-CE (SADEJ) para a prática pedagógica - Carvalho, Débora Aldyane Barbosa (2013)
Discusses the use of large-scale assessment, especially System Performance Assessment School Jaguaruana - CE (SADEJ) as a tool to improve teaching practice. The SADEJ seeks to provide information on the performance of students and teachers. The results provide interventive actions of an administrative and teaching to overcome the challenges identified by the evaluative act. Indeed, part of the understanding that assessment, when used as a guiding instrument for learning management, can contribute to pedagogical practice and improve the quality of teaching and hence learning itself. Thus, the study aimed to understand the impact of the results derived by SADEJ to improve pedagogical practice and the management of learning in basic education in public schools Jaguaruana-CE, between 2011 and 2012. Specifically have the following objectives: to describe the structure from the creation and deployment of evaluative experience in schools to the methodology of collection, treatment, presentation of data, analyze how the Department of Education appropriates the results obtained by the proposed evaluation to restructure administrative and pedagogical actions; explicit, in the perception of teachers, the implications of the system in teaching activities; SADEJ evaluate the contributions of the observed performance in elementary school. The methodology followed the approach of quantitative-bibliographical and field. For data collection, we resorted to the use of semi-structured interviews and questionnaires. As a resource to understand the results, we used, respectively, the content analysis (RODRIGUES) for responses issued and SPSS (Statistical Package for the Social Sciences) version 15.0 Windows application for analysis of the questionnaire. The sample consisted of 129 subjects who teach in elementary schools in the municipal education Jaguaruana-CE seven team members SADEJ. The results show that the large-scale assessment by itself, does not improve student performance, nor learning, but the actions subsequent to this type of evaluation which uses the results to inform decisions can contribute to the quality of teaching and optimization performance indicators and learning. This contribution to the pedagogical practice was evident in the proposed SADEJ. The impact of the actions taken after the disclosure of the results is sensitive in growth rates as measured by the indicators and the Proof IDEB Brazil.